Representasi Pergolakan Batin Perempuan dalam Film Little Women (Analisis Wacana Kritis Sara Mills) - Sigit Surahman; Ignasius Liliek Senaharjanta; Shella Fendisa (Institut Seni Indonesia Yogyakarta, 2022)
The issue of gender is still a debate in society today. Women cannot enjoy a free life, and are often constrained to follow the rules that exist in society. Film as one of the mass media that can convey messages widely, has become a medium used by feminist fighters to raise the issue. One of them is Greta Gerwig's Little Women. The film tells the story of the author's life journey with 3 sisters, each of whom has a dream when they grow up, but has to deal with the rules that limit them, which of course becomes an inner struggle for the March brothers, between achieving their dreams or living in a marriage. The researcher uses a qualitative approach, with Liberal Feminism Theory and Sara Mills Critical Discourse Analysis to analyze the film based on the position of the subject, object, and audience. Intended to find discrimination, as well as stereotypes contained in the film, as the cause of the inner turmoil of women in the film Little Women. The conclusion of this film represents the position of women as marginalized and not getting equal opportunities with men. Various aspects of life limit women's space for movement and place women in a women's social construction, causing inner turmoil in living life between following their wishes, or the rules in society.